Evaluation of the Lessons Learned from the Corona Pandemic (Covid-19) And Their Reflection on Reshaping the Strategic Priorities of Jordanian Private Universities - Salih, Ahmad; Nasereddin, Ahmad (The Arab Journal of Administration, 2023)
The current study aimed to evaluate the lessons learned from the Corona pandemic (Covid-19), and how these lessons reflected on reshaping the strategic priorities of Jordanian private universities. The study population consisted of (3211) faculty members of different academic ranks, from (19) universities that make up the total number of Jordanian private universities either the sample was a simple random sample that consisted of (344) respondents. The study used questionnaire and interviews as prime tools in collecting data and information that were analyzed using Structural Equation modelling (SEM) through (AMOS-21) software. The most important results of the study the sample evaluation of the identified lessons learned and the trends towards reshaping strategic priorities was high, and there was a statistically significant impact of the (combined) lessons of the Corona pandemic on reshaping the strategic priorities of Jordanian private universities. The most prominent recommendations were to enhance investment in digital capital and extend it at the level of intellectual structures and infrastructure. Besides, intensify efforts to increase the practices of strategic thinking and planning management.